Monitoring treatment in pediatric patients with 21-hydroxylase deficiency - Itonaga, Tomoyo; Hasegawa, Yukihiro (Frontiers in Endocrinology, 2023)
21-hydroxylase deficiency (21-OHD) is the most common form of congenital adrenal hyperplasia. In most developed countries, newborn screening enables diagnosis of 21-OHD in asymptomatic patients during the neonatal period. In addition, recent advances in genetic testing have facilitated diagnosing 21-OHD, particularly in patients with equivocal clinical information. On the other hand, many challenges related to treatment remain. The goals of glucocorticoid therapy for childhood 21-OHD are to maintain growth and maturation as in healthy children by compensating for cortisol deficiency and suppressing excess adrenal androgen production. It is not easy to calibrate the glucocorticoid dosage accurately for patients with 21-OHD. Auxological data, such as height, body weight, and bone age, are considered the gold standard for monitoring of 21-OHD, particularly in prepuberty. However, these data require months to a year to evaluate. Theoretically, biochemical monitoring using steroid metabolites allows a much shorter monitoring period (hours to days). However, there are many unsolved problems in the clinical setting. For example, many steroid metabolites are affected by the circadian rhythm and timing of medication. There is still a paucity of evidence for the utility of biochemical monitoring. In the present review, we have attempted to clarify the knowns and unknowns about treatment parameters in 21-OHD during childhood.